The job satisfaction level analysis for the research environment and the research production - Donghun Yoon (Cogent Business & Management, 2020)
The most important factor of the competitiveness of South Korea's national science and technology is the research results. University professors and national research institute researchers perform the important role of generating research results. Therefore, the responsibilities and missions of university professors and national research institute researchers are growing constantly. University professors perform knowledge creation and education. National research institute researchers support national science policy-making and the government R&D program. Satisfactory research support and research environments are very important for university professors and national research institute researchers. Thus, this paper analyzes the job satisfaction level of university professors and national research institute researchers with regard to their research environment and research production. It also proposes an effective policy for achieving a satisfactory research environment based on the results of an analysis of research environments and research production.
Keywords: 650; national science and technology; R&D efficiency; research production; research environment; job satisfaction; researcher; professor